Structural basis for assembly and function of the Nup82 complex in the nuclear pore scaffold - Gaik, Monika; Flemming, Dirk; Mücke, Norbert; Fischer, Jessica; Stelter, Philipp; Baßler, Jochen; Hurt, Ed (The journal of cell biology, 2015)
Nuclear pore complexes (NPCs) are huge assemblies formed from ∼30 different nucleoporins, typically organized in subcomplexes. One module, the conserved Nup82 complex at the cytoplasmic face of NPCs, is crucial to terminate mRNA export. To gain insight into the structure, assembly, and function of the cytoplasmic pore filaments, we reconstituted in yeast the Nup82-Nup159-Nsp1-Dyn2 complex, which was suitable for biochemical, biophysical, and electron microscopy analyses. Our integrative approach revealed that the yeast Nup82 complex forms an unusual asymmetric structure with a dimeric array of subunits. Based on all these data, we developed a three-dimensional structural model of the Nup82 complex that depicts how this module might be anchored to the NPC scaffold and concomitantly can interact with the soluble nucleocytoplasmic transport machinery.
Gesehen am 06.08.2021